PEREIRA, Rosalie Helena de Souza. Averróis: A Arte de Governar - Iskandar, Jamil Ibrahim (REVER: Revista de Estudos da Religião, 2013)
Resenha do livro PEREIRA, Rosalie Helena de Souza. Averróis: A Arte de Governar